Leigh Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs)
Histologic and biochemical analyses of muscle biopsies from 33 patients with Leigh encephalopathy were performed at the National Institute of Neuroscience, Tokyo and Tokushima University School of Medicine, Japan.